CORRELATION BETWEEN KNOWLEDGE, ATTITUDE AND BEHAVIOUR TOWARDS RIVER POLLUTION - Norshahida Akma Alias (INTERNATIONAL JOURNAL OF MODERN TRENDS IN SOCIAL SCIENCES (IJMTSS), 2024)
Lately, environmental issues are seen as one of the serious issues plaguing the world’s population detected. One issue is the pollution of the river. This study aimed to determine the relationship between knowledge and attitude toward the behaviour of river pollution. Research conducted the survey method through the use of questionnaires as instruments to collect data on knowledge, attitudes, and behaviour of river pollution. A total of 150 respondents participated in the study. The results showed that knowledge and attitude have a significant correlation with the behaviour of river pollution. Although both variables have seen significant relationships on knowledge there is a more powerful influence on behaviour than attitude pollution.